Self-Assembling Metabolon Enables the Cell Free Conversion of Glycerol to 1,3-Propanediol - Xu, Qi; Alahuhta, Markus; Hewitt, Patrick; Sarai, Nicholas S.; Wei, Hui; Hengge, Neal N.; Mittal, Ashutosh; Himmel, Michael E.; Bomble, Yannick J. (Frontiers in Energy Research, 2021)
Cell free biocatalysis is showing promise as a replacement or complement to conventional microbial biocatalysts due to the potential for achieving high yields, titers, and productivities. However, there exist several challenges that need to be addressed before its broader industrial adoption is achieved. New paradigms and innovative solutions are needed to overcome these challenges. In this study we demonstrate high levels of glycerol conversion to 1,3-propanediol using a self-assembling metabolic pathway leveraging the arraying strategy (protein scaffolds) used by thermophilic cellulolytic bacteria to assemble their biomass degrading enzymes. These synthetic metabolons were capable of producing 1,3-PDO at a yield more than 95% at lower glycerol concentration and close to 70% at higher concentrations at a higher productivity rate than the equivalent microbial strain. One of the benefits of our approach is the fact that no enzyme purification is required, and that the assembly of the complex is accomplished in vivo before immobilization, while product formation is conducted in vitro. We also report the recovery of enzymatic activity upon fusion enzymes binding to these protein scaffolds, which could have broader applications when assembling arrayed protein complexes.